Помогите, пожалуйста! Очень нужно

0 голосов
52 просмотров

Помогите, пожалуйста! Очень нужно


image

Алгебра (6.8k баллов) | 52 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
B1. 
f'= \frac{x^{2}-2x*(x-1)}{x^{4}}=\frac{x^{2}-2x^{2}+2x}{x^{4}}=\frac{-x^{2}+2x}{x^{4}}=\frac{2-x}{x^{3}}=0

\frac{2-x}{x^{3}}=0 => x=2,x \neq 0

Ответ: при х=2

B2.
Y(x)=y(x_{0})+y'(x_{0})*(x-x_{0}) - общее уравнение касательной
y(x_{0})=y(1)=1
y'(x)=3*(2x-1)^{2}*2=6*(2x-1)^{2}
y'(1)=6*(2-1)^{2}=6

Y(x)=1+6x-6=6x-5 - уравнение касательной
(63.2k баллов)